Influence of porosity and hBN content on the damping capacity of metal matrix composites. (14th March 2020) - Paz, G.A.R.; Campos, B.H.A.; Souza, P.H.G.; Neves, G.O.; Binder, C.; Klein, A.N.
ABSTRACT: Sintered iron samples were produced using different pressing loads, resulting in different residual porosities of approximately 14%, 18%, 22% and 30%. Iron-matrix composites, containing 2.5, 5.0, 7.5 and 10.0 %vol. of dispersed hexagonal boron nitride (hBN) particles, were also produced. The influence of these parameters on the amplitude-dependent damping capacity was assessed using a dynamic-mechanical analyser. The simultaneous effect on mechanical strength was assessed through a tensile test. The microstructure was analysed with optical and electronic microscopy and quantitatively evaluated through a digital image analysis. It was verified that the increase of porosity did not lead to a representative increase in the damping capacity of sintered iron. On the other hand, higher hBN content leads to a higher damping capacity due to the introduction of robust new damping mechanisms. However, hBN reservoirs, which are bigger and more elongated than the pores, are more detrimental to mechanical strength.